Analysis of Bali Tourism Data to Map the Potential of Tourism Objects - Rizki Mawan; M. Rinandar Tasya; Dimas Wiryatari (CCIT Journal, 2020)
Tourism can not be separated from human life. The last few years tourism has become a culture for modern society both locally and abroad. To increase the potential of tourist attractions can be known by the presence of public facilities around it such as hospitals, restaurants, banks, Gas Stations, bars, shops, hotels and coffee. The purpose of this study was to determine how the influence of these facilities in the potential to increase the number of visitors. To determine the effect of public facilities available on attractions in the potential to increase visitor attraction, it must be known how far the facilities are from attractions and whatfacilities are in the vicinity of these attractions. The distance between facilities on the tourist attraction can be calculated using a predetermined formula. The most visited tourist attraction is Taman Budaya which is located in Denpasar Regency with a total of 7.500 visits from 2013- 2018. The most visited nationalities in Bali in 2018 are Middle East and the State of Turkey which is 9,247. Tourists visit Bali through 2 modes of transportation. The 2 modes of transportation are water and air. The total number of visitors with the mode of water transportation was 20,460,556.00 while the air transport mode was 237,428.00.